A Music-Mediated Language Learning Experience: Students’ Awareness of Their Socio-Emotional Skills - Cores-Bilbao, Esther; Fernández-Corbacho, Analí; Machancoses, Francisco H.; Fonseca-Mora, M. C. (Frontiers in Psychology, 2019)
In a society where mobility, globalization and contact with people from other cultures have become its basic descriptors, the enhancement of plurilingualism and intercultural understanding seem to be of the utmost concern. From a Positive Psychology Perspective, agency is the human capacity to affect other people positively or negatively through their actions. This agentic vision can be related to mediation, a concept rooted in the socio-cultural learning theory where social interaction is considered a fundamental cornerstone in the development of cognition. Social interactions in the language learning setting may be facilitated through musical activities due to its social bonding effect. This paper tries to offer insights on how a musical-mediated experience in language learning may develop students’ interpersonal and collaborative competences to become active members of a more inclusive society. Mediation, considered as a paradigm shift in the foreign language classroom and the different out-of-class language learning possibilities, could also provide an environment where learners maximize their emotional intelligence. Our paper focuses on this paradigm shift spearheaded by the CEFR Companion Volume and the considerable repercussions it is bound to have for foreign language didactics, as cooperative tasks become central to foreign language learning. We hypothesize that mediated language learning experiences imply a socioemotional change in learners, focusing on the others, on their needs and interests, by trying to help them understand texts, concepts or facilitating communication with their peers. An intervention with a musical-mediated language learning experience was designed and implemented in the classroom. A self assessment scale with mediation descriptors and the socioemotional expertise scale (SEE) were administered. Results show that students become more mindful of their strengths, of their capacity for collaborating and team working. This leads to more awareness of their mediation skills. Students’ mediation skills correlate significantly with their socio-emotional skills, more concretely with their expressivity. The implementation of a musical-mediated experience also promoted tolerance and enhanced learners’ intrinsic motivation for language learning at the same time as they acknowledged their diversity.